PENGARUH PEMAHAMAN MATERI SHALAT BERJAMAAH TERHADAP KEAKTIFAN SHALAT BERJAMAAH PADA SISWA KELAS VII MTS. MUHAMMADIYAH 10 DESA GROGOL KECAMATAN SAWOO KABUPATEN PONOROGO TAHUN PELAJARAN 2016/2017 - Novi Lestari; Ahmad Muslich; Ayok Ariyanto (TARBAWI:Journal on Islamic Education, 2017)
The comprehension toward the material of prayer has to be taught and trained to the students. One of the sub topic included in the material of prayer is the material of prayer in congregation. The research conducted based on the background of phenomenon in education that many students comprehend the material cognitively, and also able to practice skillfully, but they have no will or affective awareness to apply their comprehension and skill in their daily life. The similar condition to the comprehension of prayer, especially prayer in congregation. The students who study in Junior High School already studied the material of prayer in congregation. But not all of them have a will or awareness to conduct prayer in congregation in daily life. This problem encourages the researcher to conduct the research.The purpose of the research is firstly to figure out the students’ comprehension toward the material of prayers in congregation. Secondly, it purposes to figure out the students’ activity toward their prayers in congregation. And the third purpose is to find out the influence of students’ comprehension of prayer in congregation toward the student’ activity in prayer in congregation.The research is a correlation quantitative research. It is conducted in MTs Muhammadiyah 10 Ponorogo. The sample taken for the research is the 7th grade students in academic year 2016/2017. The methods of collecting data are observation, questionnaire, interview, and documentation method. The tech-niques of analyzing data are technique of descriptive percentage and product moment analysis.The result of the research shows that 1). The students comprehension toward the material of prayer in congregation consists of three categories, nomination A or very good category has 48% (14 students), nomination B or good category has 17% (5 students), and nomination C or middle category has 35 % (10 students). 2). The students activity toward prayer in congregation consists of three categories, they are nomination A or active category covers 31% (9 students), nomination B atau enough category has 48% (14 students), and nomination C or less active has 21% (6 students). 3). The result obtained from the coefficient of variabel X (students comprehension toward material of prayer in congregation) and variabel Y (students activity in prayer in congregation) with product moment analysis is 0,584. Whereas rtable on the significance level 1% is 0,470. Thereby the result is significant as the correlation coefficient is higher than the poin r of product moment table (0,584 0,470). Thus it can be concluded that there is a positive influence of students’ comprehension in the material of prayer in congregation toward the students’ activity in prayer in congregation.